Penerapan Metode Eksperimen Dalam Pembelajaran IPA Untuk Meningkatkan Keterampilan Proses Sains - Toni Abdulah Noor; Rizki Hadiwijaya Julkarnaen; Winarti Dwi Febriani (Lencana: Jurnal Inovasi Ilmu Pendidikan, 2024)
This research aims to improve students' science process skills using experimental methods. This research method is classroom action research (PTK). Kemmis and Mc Taggart PTK model. This research was carried out in 2 cycles consisting of planning, implementation, observation and reflection. Learning implementation plan sheet, educator and student observation sheet. For science process skills using tests and documentation. The population in this study were all class V students at Pasircuri Elementary School, Tasikmalaya Regency, totaling 17 people. The average score for Pre-action Science learning was (48.2), cycle I (64.1) and cycle II (85.2). The pre-action science process skills of 3 students (15%) were completed and 14 students (85%) were incomplete with an average of 48.2. As a result of improving science process skills in cycle I, there were 11 students (64%) who had completed it and 6 students (36%) who had not completed it with an average of 64.1. In cycle II there were 14 students (82%) who completed and 3 students (18%) who did not complete with an average of 85.25. Thus there is an increase with each cycle (65%) with experimental methods to improve students' science process skills.